Estradiol metabolites as biomarkers of endometrial cancer prognosis after surgery. Issue 178 (April 2018) - Audet-Delage, Yannick; Grégoire, Jean; Caron, Patrick; Turcotte, Véronique; Plante, Marie; Ayotte, Pierre; Simonyan, David; Villeneuve, Lyne; Guillemette, Chantal
Highlights: We studied 246 newly diagnosed postmenopausal EC cases treated by hysterectomy. 27 steroids were profiled in pre- and post- operative serums by MS. Preoperative E3 and E1 -S levels were inversely related to recurrence. Higher postoperative 4-MeOE2 was linked to a lower risk of recurrence. Estrogen metabolites represent potential independent prognostic factors. Abstract: Endometrial cancer (EC) is the most common gynecologic malignancy prevailing after menopause. Defining steroid profiles may help predict the risk of recurrence after hysterectomy, which remains limited due to the lack of reliable markers. Adrenal precursors, androgens, parent estrogens and catechol estrogen metabolites were measured by mass spectrometry (MS) in preoperative serums and those collected one month after hysterectomy from 246 newly diagnosed postmenopausal EC cases. We also examined the associations between steroid hormones and EC status by including 110 healthy postmenopausal women. Steroid concentrations were analyzed in relation to clinicopathological features, recurrence and overall survival (OS). The mean follow-up time was 65.5 months and 26 patients experienced relapse after surgery for a recurrence incidence of 10.6% (6.4% Type I and 29.5% Type II). Recurrence and OS were related to a more aggressive disease but not linked to body mass index. Preoperative levels of estriol (E3 ) and estrone-sulfate (E1 -S) were inversely associated with recurrence in a multivariate logistic regression analysis (Hazard ratios (HRs) of 0.31, P = 0.039 and 3.01, P = 0.024; respectively). All circulating steroids declined considerably after surgery almost reaching those of healthy women, except 4-methoxy-E2 (4MeO-E2 ) for which postoperative levels increased by 35% and were associated to a 68% decreased risk of recurrence (HR = 0.32, P = 0.015). Women diagnosed with both histological types of EC present significantly higher levels of steroids, in support of their mitogenic effects. The estrogen precursor E1 -S, the anticancer metabolite 4MeO-E2, and E3 that exert mixed antagonist and agonist estrogenic activities and immunological effects, are potential independent prognostic factors.